2014
DOI: 10.1007/s10126-014-9608-6
|View full text |Cite
|
Sign up to set email alerts
|

Preferential Expression of a Bromoperoxidase in Sporophytes of a Red Alga, Pyropia yezoensis

Abstract: A 2,158 bp cDNA (PyBPO1) encoding a bromoperoxidase (BPO) of 625 amino acids was isolated from Pyropia yezoensis. Phylogenetic analysis using amino acid sequences of BPOs suggested that P. yezoensis and cyanobacteria were grouped in the same clade and separated from brown algae. Genomic Southern blot analysis suggested that PyBPO1 existed as a single copy per haploid genome. RT-PCR revealed that PyBPO1 was actively expressed in filamentous sporophytes but repressed in leafy gametophytes under normal growth con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 56 publications
0
4
0
Order By: Relevance
“…Therefore, we first evaluated the expression of thallus- and conchocelis-specific genes in the conchosporangium by quantitative reverse-transcriptase PCR (qRT-PCR). Previous reports have shown that genes encoding the alginate lyase (PyAly) 25 , sodium pump (PyKPA2) 26 , and ammonium transporter (PyAMT1) 27 are thallus specific, whereas genes encoding the sodium pump (PyKPA1) 28 , bromoperoxidase (PyBPO) 29 , and urea transporter (PyDUR3.3) 30 are conchocelis specific. Thus, we compared the expression levels of these genes in the thallus, conchosporangium, and conchocelis by qRT-PCR with gene-specific primers (Supplementary Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, we first evaluated the expression of thallus- and conchocelis-specific genes in the conchosporangium by quantitative reverse-transcriptase PCR (qRT-PCR). Previous reports have shown that genes encoding the alginate lyase (PyAly) 25 , sodium pump (PyKPA2) 26 , and ammonium transporter (PyAMT1) 27 are thallus specific, whereas genes encoding the sodium pump (PyKPA1) 28 , bromoperoxidase (PyBPO) 29 , and urea transporter (PyDUR3.3) 30 are conchocelis specific. Thus, we compared the expression levels of these genes in the thallus, conchosporangium, and conchocelis by qRT-PCR with gene-specific primers (Supplementary Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…A differential expression of haloperoxidases, which could then lead to the differential production of halogenated molecules, could explain the observed differences in the abundance of not only compound 4 but also other halogenated compounds. The preferential expression of a gene encoding for bromoperoxidase was already reported in the sporophyte stage of the red algae Pyropia yezoensis [ 33 ]. The authors showed that it was actively expressed in filamentous sporophytes, leading to bromoform production, but repressed in leafy gametophytes under normal growth conditions, which is in accordance with our hypothesis.…”
Section: Discussionmentioning
confidence: 94%
“…Our results showed that a homologue of haloperoxidase was significantly up-regulated in all infection experiments. Quantitative PCR analysis on a boromoperoxidase isolated from Pyropia yezoensis showed that it is actively expressed in filamentous sporophytes but repressed in leafy gametophytes under normal growth conditions (Matsuda et al 2015). Further studies on isolated halogenated compounds are necessary to understand their role in Pyropia defense against pathogens.…”
Section: Discussionmentioning
confidence: 99%